2017
DOI: 10.1002/phar.1983
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Human Leukocyte Antigen (HLA) Alleles and Killer Cell Immunoglobulin‐Like Receptors (KIR) Types on Heparin‐Induced Thrombocytopenia (HIT)

Abstract: Objectives Variation in human leukocyte antigen (HLA) genes is now used to prevent immune-mediated adverse drug reactions. Combinations of HLA alleles and killer cell immunoglobulin-like receptors (KIR) are associated with multiple autoimmune diseases and infections. Heparin-induced thrombocytopenia (HIT) is an unpredictable, life-threatening, immune-mediated reaction to heparin. The objective of this study is to evaluate the association of HLA alleles and KIR types, alone or in the presence of different HLA l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Other supporting data come from findings of a restricted T cell repertoire in patients with HIT 42,43 and the requirement for T cells in the murine HIT immune response. [44][45][46] Recent genome wide association (GWAS) studies, though involving small numbers of patients, identified several candidate genes, 47,48 including an HLA-DRB3*01:01 allele associated with a greater risk of developing HIT 49 ; these findings will require validation in larger cohorts.…”
Section: The Hit Immune Responsementioning
confidence: 99%
“…Other supporting data come from findings of a restricted T cell repertoire in patients with HIT 42,43 and the requirement for T cells in the murine HIT immune response. [44][45][46] Recent genome wide association (GWAS) studies, though involving small numbers of patients, identified several candidate genes, 47,48 including an HLA-DRB3*01:01 allele associated with a greater risk of developing HIT 49 ; these findings will require validation in larger cohorts.…”
Section: The Hit Immune Responsementioning
confidence: 99%
“…The HLA-types DRB1*11 and DQB1*03:01 are associated with an increased risk of thrombocytopenic thrombotic purpura, and DRB1*11 is tightly linked to DRB3*01:01, identified as a potential risk factor for the development of HIT. 20 …”
Section: Discussionmentioning
confidence: 99%
“…Anti‐HIT antibody is an antibody against the complex of platelet factor 4 and heparin, which is thought to lead to the onset of HIT. Very recently, the HLA‐DRB3 *01:01 allele was identified as a potential risk factor for HIT in people of European ancestry4. Although we did not check this allele, this allele might have been associated with the onset of HIT in this patient.…”
mentioning
confidence: 81%